Risk of soft tissue sarcomas and residence in the neighbourhood of an incinerator of industrial wastes. Issue 9 (22nd August 2003) - Comba, P; Ascoli, V; Belli, S; Benedetti, M; Gatti, L; Ricci, P; Tieghi, A
Abstract : Aims: To investigate the association between occurrence of soft tissue sarcomas (STS) in Mantua and residence near an incinerator of industrial wastes. Methods: Cases were subjects with histologically confirmed primary malignant STS diagnosed 1989–98 in the population resident in Mantua and in the three neighbouring municipalities. Controls were randomly extracted from population registries, matched for age and sex. Residential history was reconstructed for all study subjects since 1960. Main residence was geographically positioned according to GPS standards. Results: The study included 37 STS cases (17 men and 20 women) and 171 controls. The incidence of STS in the area of study was estimated as 8.8 per 100 000 in men and 5.6 per 100 000 in women. The odds ratio associated with residence within 2 km, standardised by age and sex, was 31.4 (95% CI 5.6 to 176.1), based on five exposed cases. At greater distances, risk rapidly decreased, showing a fluctuation around the null value of 1. Conclusion: The study shows a significant increase in risk of STS associated with residence within 2 km of an industrial waste incinerator; an aetiological role of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) can be hypothesised.